Opportunities of13C NMR spectroscopy of high resolution for metabolomic analysis of oral liquid (Эндодонтия Today)
NMR-spectroscopy has a growing importance in medicine as a tool for metabolic screening for abnormalities in biological fluids. Carbon is the basis of the most biologically significant molecules and13C NMR spectroscopy involves the direct measurement of these compounds. Clinical examination of patients, men and women, aged from 18 to 30 years, was carried out. Particular attention was paid to the detection of wedge-shaped defects of teeth hard tissues at various stages of this disease, as well as co-factors of its occurrence. NMR spectroscopy of carbon isotope13С nuclei of oral liquid samples from a healthy person (control) and patients with severe wedge-shaped lesions was chosen as a laboratory testing method. Studies have shown the analytical capabilities of oral liquid13C NMR spectroscopy of high resolution and promising directions for finding markers of dental diseases in their early stages.